Characterization Of Proton Conducting Carboxymethyl Cellulose/Chitosan Dual-blend Based Biopolymer Electrolytes - Mohd Saiful Asmal Rani; N.S. Mohamed; Mohd Ikmar Nizam Mohamad Isa (Trans Tech Publication, 2024)
This article presents the discovery on biopolymer electrolytes comprising of ammonium nitrate, NH4NO3 with dual-blend biopolymer materials, carboxymethyl cellulose/chitosan which were prepared via solution-casting technique. The biopolymer blend based electrolyte films were characterized by Fourier Transform Infrared spectroscopy to investigate the formation of the dual-blend biopolymer based complexes. X-Ray Diffraction result showed that all dual-blend samples were predominantly amorphous. Electrochemical impedance spectroscopy was conducted to obtain their ionic conductivities. The highest conductivity at ambient temperature of 1.03 105 S cm1 was obtained for the electrolyte film containing 40 wt% of NH4NO3. These results indicated that the dual-blend biopolymer based electrolyte has potential for application of electrochemical devices.